Development of PBL-STEM-Based Edcafe Application Learning Design in an Effort to Improve Students' Numeracy Skills and Overcome Mathematical Anxiety - Friantiani Safitri; Siti Khaulah; Bulan Nuri (Jurnal Penelitian Pendidikan IPA, 2025)
Indonesian education grapples with persistent challenges, including students' mathematical anxiety and suboptimal numeracy skills. This study concurrently addresses these issues through the development and validation of a PBL–STEM-integrated Edcafe application learning design. Aimed at high school students, this innovative approach seeks to mitigate mathematical anxiety while enhancing numeracy competencies. Adopting a Research and Development methodology framed by the ADDIE model, the study produced a comprehensive application design tailored to deliver problem-based learning within contextualized environments. Validation outcomes were highly favorable: media experts rated the statistics learning materials at 88.33% (highly valid category), material experts at 91.66% (very valid category), and practitioners at 94.09% (very practical category). Small-group trials confirmed the suitability for implementation, while large-group testing indicated that 42.86% of students strongly agreed and 53.57% expressed interest in using the Edcafe application. Collectively, the findings and expert endorsements underscore the learning materials' strong validity and utility for mathematics instruction.